Advancement in computational simulation and validation of congenital heart disease: A review - Ahmad Fikri Azfar, Ahmad Azaharia; Wan Naimah, Wan Ab Naim; Nor Ashikin, Md Sari; Lim, Einly; Mohd Jamil, Mohamed Mokhtarudin (Taylor and Francis Ltd., 2024)
The improvement in congenital heart disease (CHD) treatment and management has increased the life expectancy in infants. However, the long-term efficacy is difficult to assess and thus, computational modelling has been applied for evaluating this. Here, we provide an overview of the applications of computational modelling in CHD based on three categories; CHD involving large blood vessels only, heart chambers only, and CHD that occurs at multiple heart structures. We highlight the advancement of computational simulation of CHD that uses multiscale and multiphysics modelling to ensure a complete representation of the heart and circulation. We provide a brief future direction of computational modelling of CHD such as to include growth and remodelling, detailed conduction system, and occurrence of myocardial infarction. We also proposed validation technique using advanced three-dimensional (3D) printing and particle image velocimetry (PIV) technologies to improve the model accuracy.